2023
DOI: 10.5853/jos.2022.02936
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Circulation in Ischemic Stroke: An Updated Review

Abstract: The collateral circulation plays a crucial role in maintaining perfusion to brain tissue in ischemic stroke, which prolongs the time window for effective therapies to be provided and ultimately avoids irreversible damage that may lead to worse clinical outcomes. The understanding of this complex vascular bypass system has advanced greatly in the past few years, yet effective treatments for its potentiation as a therapeutic target remain a challenge. The assessment of the collateral circulation is now part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 115 publications
(120 reference statements)
1
27
0
1
Order By: Relevance
“…In this study, the proportion of LMC in patients with primary MeVO was significantly lower than that in patients with secondary MeVO (23% vs. 45%). We speculate that it may be related to the lower pressure gradients at the distal position 40 and the lower proportion of atherosclerotic‐related stroke in distal arterial territories 41 . The difference in collateral circulation compensation between MeVO and LVO needs further study.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the proportion of LMC in patients with primary MeVO was significantly lower than that in patients with secondary MeVO (23% vs. 45%). We speculate that it may be related to the lower pressure gradients at the distal position 40 and the lower proportion of atherosclerotic‐related stroke in distal arterial territories 41 . The difference in collateral circulation compensation between MeVO and LVO needs further study.…”
Section: Discussionmentioning
confidence: 94%
“…11 In addition to the posterior communicating artery, the anterior and posterior circulation may also be connected via direct carotid-vertebrobasilar connections, which rarely may persist beyond embryonic stages but are very important to recognize when found clinically. 11 The secondary collateral network consists of finer leptomeningeal vessels that exist as a bridge between the distal branches of the primary named cerebral vessels (between ACA-MCA regions, ACA-PCA regions, and MCA-PCA regions) and the cerebellar vessels mentioned above. 10 Studies have shown that the robustness of the network between the ACA-MCA regions is greater than that between PCA-MCA and ACA-PCA regions.…”
Section: Collateral Network Anatomymentioning
confidence: 99%
“…Such a link facilitates retrograde flow to terminal intracranial cerebral artery branches, which can maintain perfusion even with proximal occlusions of these intracranial vessels. [8][9][10][11] There also exists a tertiary system, which involves vessels established through neoangiogenesis (formation of capillaries from existing blood vessels) and arteriogenesis (de novo formation of blood vessels). 13 Angiogenesis is primarily stimulated by the release of angiogenic growth factors at the peripheries of an ischemic bed.…”
Section: Collateral Network Anatomymentioning
confidence: 99%
See 2 more Smart Citations